Cost optimization for marketing in online communities - Пелещишин, Оксана Петрівна (Eastern-European Journal of Enterprise Technologies, 2013)
Online communities in marketing provide to a company opportunities to interact with the outside world, to monitor competitors’ activity and the state of an industry. Active use of the online communities presupposes that representatives of companies participate in the life of the online communities to disseminate marketing information and tracking the reaction of society on company’s activity. Thus, the accounting and control of resources are very important for marketing activities in virtual environments. The article studies the structure of costs on activities of its members in the online communities. The influence of the chosen strategy of the online communities in marketing on the components of costs was analyzed. The control of cost budget in the selection of the online communities for market specialists to participate there enables usage of the allocated resources, covering the major theme communities. To find the optimal allocation of human resources among sites of the online communities the mathematical model was built based on the estimation of labor costs for various types of work. This model minimizes the cost of marketing activities in online communities